Pertumbuhan Ekonomi dan Strategi Pengembangan Startup di Indonesia - Vitriyah, Nurul Lailatul (KUBIS, 2023)
The impact of economic growth with the role of technology that leads to startups and support of the 1000 startup movement and determination of achievement of government's vision to make Indonesia as The Digital Energy of Asia in 2020 provides enormous opportunities for new startups. This study aims to find the critical success factors in young startups that have just been generated by using SWOT analysis (Strengths, Weakness, Oportunities, Threat) and in a descriptiongenerated by using SWOT analysis (Strengths, Weakness, Oportunities, Threat) and in a description describing startup businesses in Indonesia. Based on the results of the analysis there is a conclusion that funding, innovation in new fields and promotion can be a successful strategy for startups in Indonesia.